Hydration in aqueous NaCl - Sahle Christoph J.; de Clermont Gallerande Emmanuelle; Niskanen Johannes; Longo Alessandro; Elbers Mirko; Schroer Martin A.; Sternemann Christian; Jahn Sandro (Royal Society of Chemistry, 2022)
Atomistic details about the hydration of ions in aqueous solutions are still debated due to the disordered and statistical nature of the hydration process. However, many processes from biology, physical chemistry to materials sciences rely on the complex interplay between solute and solvent. Oxygen K-edge X-ray excitation spectra provide a sensitive probe of the local atomic and electronic surrounding of the excited sites. We used ab initio molecular dynamics simulations together with extensive spectrum calculations to relate the features found in experimental oxygen K-edge spectra of a concentration series of aqueous NaCl with the induced structural changes upon solvation of the salt and distill the spectral fingerprints of the first hydration shells around the Na+- and Cl−-ions. By this combined experimental and theoretical approach, we find the strongest spectral changes to indeed result from the first hydration shells of both ions and relate the observed shift of spectral weight from the post- to the main-edge to the origin of the post-edge as a shape resonance.